Teacher Management In Overcoming Students With Emotional Disorders At Slb N Bireuen - Marsitah, Iis; Nurmalita, Nurmalita; Ahya, Nurul; Innaya, Innaya; Silvina, Silvina (Sean Institute, 2022)
The purpose of this research isto find out how teachers manage to deal with students who experience emotional disturbances in Bireuen State SLB. This study was designed using a qualitative approach. The samples used in this study were four Bireuen State SLB teacher respondents. In collecting this data using interview and observation methods. The results of this study indicate that the teacher's way of dealing with students who experience emotional disturbances is by conducting an assessment of appropriate and problematic social behavior in individual students. The teacher must be able to recognize the characteristics of each child, because the characteristics of different children also require different methods and approaches used in the process of mentoring learning activities to achieve learning objectives properly.